Guinea : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2004)
This paper reviews the Progress Report for Guinea's Poverty Reduction Strategy Paper (PRSP). Several measures were taken at the institutional, technical, and human levels to improve the mobilization of fiscal resources. In the monetary area, the government continued to use indirect instruments to control liquidity: reserve requirements, open market operations, treasury bills, and lead interest rates. In the area of transportation and public works, priority was given to road transport by opening up access to production areas, improving the conditions of passenger transport, and strengthening the competitiveness of the national economy.